Pengaruh Private Brand Strategy Terhadap Brand Equity Dan Implikasinya Pada Shopping Preference Konsumen Giant Supermarket Sindangbarang Bogor - Mubarak, Mumuh Mulyana (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2012)
The objective of this study is to know and to analyze the influence of private label to brand equity, the influence of brand equity to consumersâ shopping preference, and the influence of private label to consumersâ shopping preference. The respondents are the consumers of GIANT Supermarket Loji Sindangbarang Bogor. Data was collected mostly in survcey by providing questionaire and documentation study. Data processing was done by using SMARTPLS software. The result of this study shows that there is significant influence of private label to brand equity of GIANT Supermarket Loji Sindangbarang Bogor; there is significant influence of brand equity to consumersâ shopping preference; and there is significant influence of private label to consumersâ shopping preference.